Իրանա–իրաքյան պատերազմի հասարակական–քաղաքական արձագանքները - Սամվելյան, Կարինե («Զանգակ - 97»)
The Iran-iraqi war had certain impact on the social-political life of Iraq and Iran. Among the significant social-political factors of regional importance was the problem of the peace. The article deals with the analyses of the social-political consequences of the Iran-Iraqi war, the absurd character of this conflict, deslroying the two countries.
Keywords: Պատմություն